A comprehensive thermodynamic analysis of load‐flexible CHP plants using district heating network. (28th May 2019) - Sun, Yang; Xu, Cheng; Xu, Gang; Zhang, Huishuai; Li, Bin; Yang, Yongping
Summary: Because of the rapid expansion of intermittent renewable energy, conventional coal‐fired power plants, including combined heat and power (CHP) plants, are required to improve the quick‐response ability to respond the changing demand of the grid. However, the flexibility of CHP plants is not easy to be improved because of the restriction of traditional load variation mechanism. This work presents a comprehensive thermodynamic analysis on the flexibility‐improving scheme using the thermal energy storage (TES) capacity of district heating (DH) network. A typical CHP plant and related DH network were selected as a case study. The flexibility demand under the context of renewables accommodation in the short timescale (counted by minutes) and the operational characteristics of CHP plants were analyzed on the basis of experimental data and thermodynamics. Besides, the influence of heat supply adjustment on heat users' indoor temperature was quantified with a dynamic model, and the thermal inertia of the DH network is discussed. Moreover, a thermodynamic model for the load variation processes simplified with operational characteristics was established to analyze the response ability improvement of CHP plants. Results of the case study show, the scheme can shorten approximately 34% of the response time while almost have no influence on the indoor temperature of heat users. Abstract : A comprehensive thermodynamic analysis on the minute‐interval flexibility‐improving scheme for CHP plants using the heat inertia of the district heating (DH) network is performed. The distinction on energy sensitivity between the plant and DH sides of CHP is revealed on the basis of the basic thermodynamic and heat transfer theories. A thermodynamic method for evaluating load variation process is established on the basis of both the energy conversion characteristics and experimental dynamic performance of the power plant.